PENGGUNAAN MEDIA PEMBELAJARAN SMART BOX TERHADAP PENINGKATAN HASIL BELAJAR SISWA FASE A PADA MATA PELAJARAN IPS - Nadila Maulidina; Azni Faulia; Dita Oktaviani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The use of smart boxes as learning media is a solution by providing more interesting and fun learning material. Social studies learning which tends to be abstract and complex requires a more interesting approach so that students can understand the material more easily. The aim of this research is to find out how smart box learning media is used to produce learning outcomes for phase A students. The method used in this writing is a descriptive-qualitative research method which involves observation, analysis, observations, interviews, and describing an event or phenomenon. that occurs in a research object. The results of this research show that the impact of using Smart Box learning media can result in an increase in phase A student learning outcomes in social studies subjects.